Reassessing the roles of women as 'makers' of medieval art and architecture
1 online resource (2 volumes)
Keywords: These volumes propose a renewed way of framing the debate around the history of medieval art and architecture to highlight the multiple roles played by women. Today’s standard division of artist from patron is not seen in medieval inscriptions—on paintings, metalwork, embroideries, or buildings—where the most common verb is 'made' ( fecit ). At times this denotes the individual whose hands produced the work, but it can equally refer to the person whose donation made the undertaking possible. Here twenty-four scholars examine secular and religious art from across medieval Europe to demonstrate that a range of studies is of interest not just for a particular time and place but because, from this range, overall conclusions can be drawn for the question of medieval art history as a whole. Contributors are Mickey Abel, Glaire D. Anderson, Jane L. Carroll, Nicola Coldstream, María Elena Díez Jorge, Jaroslav Folda, Alexandra Gajewski, Loveday Lewes Gee, Melissa R. Katz, Katrin Kogman-Appel, Pierre Alain Mariaux, Therese Martin, Eileen McKiernan González, Rachel Moss, Jenifer Ní Ghrádaigh, Felipe Pereda, Annie Renoux, Ana Maria S. A. Rodrigues, Jane Tibbetts Schulenburg, Stefanie Seeberg, Miriam Shadis, Ellen Shortell, Loretta Vandi, and Nancy L. Wicker.